(3ahGFO GdahGFOs - (3CHh HcQ eMeO Hf ESMGb Hf NRjeIs
(3ChdgG (B:s
(3CNHQfG GdMGaX CHh GdMLGL jhSa Hf GdeRi deG cGf jhe CMO CUjH ef GdGfUGQ CQHYI hSHYhf QLdkG s
(3BNQgG (B:s
(3Yf efUhQ Yf GHQGgje Yf GdCShO Yf YGFTI bGdJ (B( (3cfJ CZJSd CfG hQShd Gddg Udi Gddg Ydjg hSde ef EfGA hGMO hfMf LfHGf (B) (3BNQ GdLRA hGdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3HBNQg SeGYs
(3LRA efg hajg KdGKI YTQ MOjKkG ef GdehGabGJs
(3eUOQ GbJfGA GdCUd (B:s
(3GdBUajI HMjOQ CHGO (B((3MOjK (B1167(2)) s
Keywords: (3GdMOjK h GdeUWdMs